2013
DOI: 10.1007/s00198-013-2468-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal vitamin D status in pregnancy and offspring bone development: the unmet needs of vitamin D era

Abstract: Data from animal and human studies implicate maternal vitamin D deficiency during pregnancy as a significant risk factor for several adverse outcomes affecting maternal, fetal, and child health. The possible associations of maternal vitamin D status and offspring bone development comprise a significant public health issue. Evidence from randomized trials regarding maternal vitamin D supplementation for optimization of offspring bone mass is lacking. In the same field, data from observational studies suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 57 publications
1
37
0
3
Order By: Relevance
“…16 Vitamin D-deficient rats deliver babies with altered brain structures consistent with increased risk of schizophrenia development. 17 Finally, although some animal studies have suggested that the mineralization of the fetal skeleton is independent of vitamin D, 18 others have observed skeletal mineralization defects in fetuses born from vitamin D-deficient or vitamin D receptornull mothers on normal calcium diets. 19 The caveat is that if the intervention was dietary or mice without vitamin D receptors were used, vitamin D deficiency in the animals was extreme, causing the animals to be highly (or totally) vitamin D deficient.…”
Section: Studies In Experimental Animalsmentioning
confidence: 99%
“…16 Vitamin D-deficient rats deliver babies with altered brain structures consistent with increased risk of schizophrenia development. 17 Finally, although some animal studies have suggested that the mineralization of the fetal skeleton is independent of vitamin D, 18 others have observed skeletal mineralization defects in fetuses born from vitamin D-deficient or vitamin D receptornull mothers on normal calcium diets. 19 The caveat is that if the intervention was dietary or mice without vitamin D receptors were used, vitamin D deficiency in the animals was extreme, causing the animals to be highly (or totally) vitamin D deficient.…”
Section: Studies In Experimental Animalsmentioning
confidence: 99%
“…Dados da literatura baseados em estudos observacionais demonstram a existência associação entre os níveis séricos maternos de VD e desfechos adversos na gestação, incluindo PE, DMG, parto prematuro ou RN pequenos para a idade gestacional (PIG), BPN, restrição de crescimento, infecção do trato respiratório, homeostase [39][40][41][42][43][44][45] . A deficiência de VD está associada a um aumento importante na incidência de desfechos neonatais adversos, como RN PIG e hipoglicemia neonatal 46 .…”
Section: Desfechos Materno-fetaisunclassified
“…Por outro lado, os estudos de suplementação forneceram evidências de que a VD tem efeitos benéficos na homeostase do cálcio neonatal. No entanto, uma série de questões, como as dificuldades técnicas dos atuais ensaios de VD e a interação funcional entre analitos de VD, proíbe a chegada a conclusões seguras 39 . As diferenças entre diversos resultados observacionais e de suplementação pode ser atribuída a diversos fatores, a saber: (i) estudo do design (falta de um resultado específico em conjunto com o tempo de suplementação, inscrição de participantes com status heterogêneo de VD); (ii) armadilhas na interpretação do equilíbrio da VD (falta de determinação da meia-vida plasmática); (iii) regime de suplementação (administração de uma ampla gama de regimes, em termos de dose, bolus e forma); (iv) características geográficas (as necessidades de VD podem variar significativamente em um país, particularmente em áreas com uma ampla faixa de gradiente de latitude); (v) adaptações do metabolismo da VD durante a gravidez (a VD e o equilíbrio do cálcio são alterados durante a gravidez em comparação com o estado não grávida) e (vi) a suplementação de populações com baixos valores basais de 25[OH]D provavelmente manifestaria efeitos benéficos.…”
Section: Revista De Patologia Do Tocantins Vol 4 No 4 Dezembro 2017unclassified
See 1 more Smart Citation
“…On that basis, data from observational studies during the last decade have suggested a potential adverse effect of maternal hypovitaminosis D during pregnancy on maternal and offspring health outcomes (6,7). Gradually, interventional studies have been conducted, focusing on the potential beneficial effects of vitamin D supplementation on these outcomes.…”
Section: Introductionmentioning
confidence: 99%